Promoting Interest and Challenging Myths Regarding Training and Careers in Medical Renal Pathology: A Pathology Trainee Survey Analyzed. (21st September 2018) - Kidd, Laura; Jain, Sanjay; Bissonnette, Mei Lin; Tchakarov, Amanda; Royal, Virginie; Braunhut, Beth; Ellis, Carla
Abstract: Objectives: The Renal Pathology Society (RPS) is an international, nonprofit, medical association with the generalized goal of improvement and dissemination of knowledge regarding the pathology and pathophysiology of renal disease. The tasks of the training committee include collecting and disseminating information about renal pathology training programs and encouraging their broad availability. Methods: In preparation to achieve these goals, the training subcommittee designed a 10-question, computerized survey to query pathology trainees with regard to their knowledge of, exposure to, potential interest in, and barriers to training in renal pathology. Results: The survey was distributed to four training programs and there were 44 total responders. The vast majority of responders were senior pathology residents in academic institutions with up to three renal pathologists on faculty. The majority became aware of renal pathology as a subspecialty choice via exposure in their medical school pathology course. The majority were in training programs with a required renal pathology elective, but many only elected to participate in preparation for the board exam. When queried why responders would not consider renal pathology for a fellowship choice or career, three modifiable and two nonmodifiable barriers are summarized: nonmodifiable ("lack of interest/stronger interest in other subspecialties" and "limited job market") and modifiable ("belief of limitation to academia, " "belief of lack of variety, " and "lack of early exposure"). Conclusion: Most pathology training programs have the resources available for adequate education in medical renal pathology. However, earlier exposure and more accurate information about the job market may lead to a better understanding of (and increased interest in) the field.